Skin pectin metabolism during the postharvest dehydration of berries from three distinct grapevine cultivars. (5th March 2013) - Zoccatelli, G.; Zenoni, S.; Savoi, S.; Dal Santo, S.; Tononi, P.; Zandonà, V.; Dal Cin, A.; Guantieri, V.; Pezzotti, M.; Tornielli, G.B.
Abstract Background and Aims Postharvest dehydration is used to modify certain grape berry quality traits that affect the characteristics of wine. After harvesting, berries undergo several chemical and physical changes that often reflect ongoing or specifically activated metabolic processes, such as the modification of cell wall polymers in the skin. We compared berry skin pectin metabolism during postharvest dehydration in three Italian wine grape cultivars. Methods and Results Corvina, Oseleta and Sangiovese grapes were postharvest dehydrated under the same environmental conditions and displayed different dehydration rates. The quantitative characterisation of pectins by ion‐exchange and size‐exclusion chromatography revealed that more demethoxylation and depolymerisation occurred in the Corvina berries, which also showed the strongest induction of pectin methylesterase and polygalacturonase gene expression (by microarray analysis) and enzyme activity (by zymography). Conclusions Postharvest dehydration affected the skin pectin metabolism of grape berries to an extent different in each of the three cultivars, reflecting differences in water loss kinetics and metabolic processes. Significance of the Study This is the first description of dynamic cultivar‐specific changes in pectin metabolism during the postharvest dehydration of grape berries.